Planejamento e produção de um criostato de baixo custo para caracterização elétrica de materiais - Torsoni, G. B. [UNESP]; Carvalho, C. L. [UNESP] (My University, 2012)
Superconductor systems based on BSCCO (BiSrCaCuO) show three main structures, Bi2Sr2CuO, Bi2Sr2Ca Cu2O, and Bi2Sr2CaCu3O, with critical temperatures about 20 K, 80 K, and 110 K, respectively. Therefore, it is fundamental to characterize these systems at low temperatures. In this work it was projected a cryogenic system with capacity to reach temperatures below the liquid nitrogen temperature (77 K). Controlling the pressure on the liquid nitrogen system, according to usual thermodynamic principles, it has been possible to reach a range of temperatures above 64 K in the sample holder. With the availability of a larger temperature range, it became possible to identify at least two superconducting phases in the BSCCO system. There is a favorable cost/benefit ratio with respect to using liquid helium as the refrigerator system. Also, this cryostat provides an application of the standard p-T diagrams (Gay-Lussac law), which are studied in undergraduate courses, and can be used as a pedagogical experimental demonstration. © Sociedade Brasileira de Física. Printed in Brazil.
Planning and production of a low cost cryostat for electrical characterization of materials
Keywords: Characterization; Cryostat; Superconductor; Thermodynamic principles phase diagrams